Back to Edgeworth? Estimating the Value of Time Using Hedonic Experiences - Christian Krekel; George MacKerron (Institute of Labor Economics (IZA), 2023)
Following early economist Francis Y. Edgeworth's proposal to measure people's hedonic experiences as they go about their daily lives, we use a smartphone app that over eight years randomly asked a panel of 30, 936 UK residents (N = 2, 235, 733) about their momentary feelings and activities to estimate the value of time (V OT), a key input into cost-benefit analyses. Exploiting the randomised timing of surveys for identification, we arrive at a V OT of 12.2 (15.3) per hour of waiting, 8.4 (10.5) per hour of commuting, and 17.2 (21.5) per hour of waiting during commuting (e.g. due to congestion). This resembles estimates from studies using revealed preferences, suggesting that using hedonic experiences leads to similar results as observed behaviour. Our unique data and method also allow us to estimate the V OT for 40 other daily activities as well as their interactions. We are the first to value time (or indeed anything) using hedonic experiences in real-time, which has the potential to value other intangibles too.
Keywords: R4; D61; I31; 330; value of time; time savings; experience-sampling; experiential valuation; cost-benefit analysis; waiting; commuting